The compatibility of land tenure law in Zanzibar with Islamic principles: an analysis - Syed Abdul Kader, Sharifah Zubaidah; Othman, Ahmad Azam; Hikmany, Abdul Nasser (IIUM Press, 2016)
Zanzibar land law has been influenced by customary tenure, foreign principles and conventional land regulation. Islamic principles, being the most practiced faith in Zanzibar, are also largely reflected in the regulations and laws of land. This article examines the compatibility of the land tenure laws in Zanzibar with Islamic principles relating to land rights. A comprehensive research has been made through legislation, case laws, textbooks, journal articles, Islamic and Muslim literatures to investigate the compatibility of present land laws in Zanzibar with Islamic principles. This article has come to a conclusion that the Zanzibar land tenure law significantly conforms to Islamic principles save with some challenges facing the land tenure laws. For example, Zanzibar land law, as they presently stand, have provisions contrary to Islamic principles such as permitting interests, land monopoly and land confiscation. Hence, some recommendations are made for the Zanzibar Government to take in reforming the land tenure laws that are conformity with Islamic principles. Keywords: Islamic principles, land law, land tenure, Zanzibar